1993
DOI: 10.1183/09031936.93.06101449
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary cough suppression as an indication of symptom severity in upper respiratory tract infections

Abstract: The aim of the present study was to determine whether the ability to suppress cough voluntarily is an index of cough severity in upper respiratory tract infection. Cough was measured by means of a microphone linked to a pen recorder and subjects were instructed to voluntarily suppress cough in order to determine cough suppression time. Subjective scores of symptom severity, mood and psychological parameters were made prior to cough measurements. The baseline frequency of cough showed a distribution towards the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Therefore, although the causes are not clear, impaired cough suppression seemed to signify worse severe cough symptom in patients with URI. 64 This study provided novel ideas for the future application of the cough suppression test. Similarly, more studies could be conducted using the cough suppression test in a range of respiratory diseases such as asthma, chronic bronchitis, and so on to evaluate their use in the classification, diagnosis and treatment of these diseases.…”
Section: Recent Progresses In Clinical Applications Of the Cough Chal...mentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, although the causes are not clear, impaired cough suppression seemed to signify worse severe cough symptom in patients with URI. 64 This study provided novel ideas for the future application of the cough suppression test. Similarly, more studies could be conducted using the cough suppression test in a range of respiratory diseases such as asthma, chronic bronchitis, and so on to evaluate their use in the classification, diagnosis and treatment of these diseases.…”
Section: Recent Progresses In Clinical Applications Of the Cough Chal...mentioning
confidence: 94%
“…The cough suppression test has great potential in the evaluation of other diseases in which cough is one of the main symptoms. Hutchings et al 64 analysed whether voluntary cough suppression could be used as an index of symptom severity in URI. The study found that some of subjects suppressed coughing less than 12.6 min (cough break group), while others could suppress for more than 20 min.…”
Section: Recent Progresses In Clinical Applications Of the Cough Chal...mentioning
confidence: 99%